Analisis Transisi Penerapan Sistem Manajemen Lingkungan ISO 14001 Versi 2015 (Studi Kasus : PT.AZ) (Transition Analysis on Application of The Environmental Management System ISO 14001 2015 Version (Case Study : PT. AZ)) - Maryeska, Cut Putri; Jati, Dian Rahayu; Pramadita, Suci (Universitas Tanjungpura, 2020)
Every ISO standard will be evaluated every 5 years to decide whether a revision is needed in order to keep the relevance toward today